Novel insights in the leadership in business and economics: A post-Coronavirus update - Wadim Strielkowski; Irina Firsova; Svetlana Azarova; Irina Shatskaya (Economies, 2022)
Our world is evolving at an incredibly enormous speed and what was impossible three years ago is now a reality. The concept of leadership and leaders has also undergone profound transformations. Moreover, the recent COVID-19 pandemic caused a digital surge in the ways economic life, business, or education are perceived or conducted. The pandemic proved that small and large businesses, industries, and the whole economies can be suddenly upended by massive technological shifts. Hence, there is a need for a theoretical research update in leadership in business and economics that would bring new insights into this topic and define its place within the context of Sustainable Development Goals (SDGs). Our paper presents the novel insights for the leaders and the leadership concept in business and economics from various approaches and angles of view in the light of the COVID-19 pandemic with a focus on sustainable leadership and organizational resilience. It aims at outlying the theoretical background of leadership in business and economics after the pandemic and bringing up interesting and recent leadership case studies from all around of the world. Moreover, this paper aims as sharing the valuable insights into what it means to be a sustainable leader in business and economics, why leaders are needed, and how to become one. The main criteria of this research and its instrumentation include both the theoretical discussion based on the literature review and analysis and the empirical analysis that supports these theoretical provisions. The paper features an empirical model that assesses how business and economic leaders are searching for new ways of work and personal development during and after the COVID-19 pandemic using the own data from the 400 respondents collected in the Czech Republic and Russia. We found that the pandemic enhanced the emotional creativity of business and economic leaders and made them to invest and engage more into using new digital technologies and fundamentally altering the old ways of managing and governing their respective companies and institutions. Our results might provide valuable food for thought both for academics working on various angles of leadership, as well as for entrepreneurs and businesspeople who want to receive recent updates on the topic of leadership to use them in their daily work.
Keywords: L10; M10; M15; O31; 330; business and economics; COVID-19 pandemic; digital revolution; leadership; organization resilience; sustainable leadership